Mangosteen Flesh Condition Detector Based on Microwave Non-destructive Technique Using Spiral Resonator Sensors - Muvianto, Cahyo Mustiko Okta; Rasyda, Muhammad Afrizal G.; Ariessaputra, Suthami; Yuniarto, Kurniawan; Sasongko, Sudi Mariyanto Al; Darmawan, Budi; Ch, Syafaruddin (Jurnal Rekayasa Elektrika, 2022)
The mangosteen fruit has a characteristic thick skin, so it is difficult to know the condition of the flesh. Farmer can only know damage to the fruit flesh after the fruit skin had opened. Detection of the quality of the mangosteen flesh can be detected using a sensor capable of penetrating the thickness of the mangosteen rind. Flesh quality detection is carried out based on the S21 value (attenuation of mangosteen flesh value) using a portable device equipped with a sensor and capable of emitting microwaves. The S21 value of the fruit's flesh was measured using a spiral resonator that functioned as a sensor. The prototype device consists of an oscillator circuit, a power splitter, and a phase detector with 2507 MHz. Fruit flesh had divided into two conditions: damaged for fruit flesh with yellow sap or Translucent Flesh Disorder, and suitable condition for clean fruit flesh. The results showed that the fruit flesh had an average S21 value of 7.041 dB for damaged flesh and 6.007 dB for good flesh condition. The difference in the value of S21 had used as a reference for detecting the shape of the fruit flesh, with the detection threshold calculated by the Support Vector Machine, resulting in a threshold value of 6.712 dB.